Microstrip antenna array and electromagnetic band gap (EBG) structures - Masri, Thelaha (Penerbit UTM, 2007)
Planar and microstrip antennas’ technology has been the most rapidly developing topic and has become a favorite subject of research by many academicians, researchers and engineers throughout the globe. Just like an artist but with an extra understanding on how an antenna works, a plane piece of substrate materials with a thin copper laminates on one or both sides of the substrate gives the designers the freedom to come out with unlimited antenna designs, including methods to improve their performance. It has evolved from academic novelty to commercial reality in the past several decades and is still undergoing monumental developments due to driving factors such as newer requirements set by the latest standards, technologies, government rules and regulations and most importantly, the increasing demands of multifunctional telecommunication devises by users and markets around the globe.